Analysis of tilt by modulated speckles generated with a double aperture pupil mask - Molina Prado, Martha Lucia (2015)
We present a method based on modulated speckles to detect tilt movement of a diffusing surface. In our proposal a speckle image of the speckle produced by a reflective diffusing surface is formed by a lens having a double aperture. The double aperture yields to an interference process so that the resulting speckle distribution is fringe modulated. The tilting of the diffusing surface is mapped as a shifting of the speckle. Then, the double aperture pupil lens system maps the speckle shifting into a fringes shifting. We study the system performance in terms of the diffuser tilt. Experimental results that confirm our proposal are presented.